Laser titanium cooker and method for manufacturing the same

JP2025024658AActive Publication Date: 2025-02-20GUANGDONG MASTER GROUP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023204409
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2023-12-04
Publication Date
2025-02-20
Estimated Expiration
2043-12-04

AI Technical Summary

Benefits of technology

【0033】 従来技術と比較して、本発明が達成できる技術的効果は、以下を含む。 本発明が提供するレーザーチタン調理器具は、鍋体と鍋体の内面に設けられた非粘着塗布層を含む。前記非粘着塗布層は、超高速レーザー溶着硬化により形成されたナノ金属セラミック層である。又は、前記非粘着塗布層は、超高速レーザー溶着硬化により形成されたナノ金属セラミック層と硬化により形成されたナノセラミック新材料とが重ねられて得られる。又は、前記非粘着塗布層は、超高速レーザー溶着硬化により形成されたナノ金属セラミック層と硬化により形成されたナノセラミック新材料とが交互に複数回重ねられて構成される。その中のナノ金属セラミック層には、樹脂とシリコーンオイルを被覆するチタン金属被覆粒子が含まれ、ナノ複合セラミック粉体新材料を組み合わせ、超高速レーザー溶着硬化を経ると、チタン金属被覆粒子中の樹脂とシリコーンオイルが効果的に塗布層中に貯蔵することができ、当該ナノ金属セラミック層が高硬度と非粘着性の効果を兼ね備えるようにする。前記ナノセラミック新材料は、ポリメチルシロキサン、ヒドロキシシリコーンオイル、低融点ガラス粉、シリカゾル、窒化ケイ素、ナノチタニア、ナノアルミナ、ナノチタンなどの成分の組み合わせにより、硬化のプロセスによりナノセラミック層表面に形成され、同様に高硬度と非粘着性の効果を有する。好ましい態様では、ナノ金属セラミック層とナノセラミック新材料が交互に重ねられ、非粘着塗布層の高硬度、耐摩耗性、持久的非粘着性の効果を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024658000001_ABST
    Figure 2025024658000001_ABST
Patent Text Reader

Abstract

To provide a laser titanium cooker and a method for manufacturing the same that are related to a technical field of a super wear resistant carbide cooker.SOLUTION: A laser titanium cooker includes: a pot body 10; and a non-adhesive coating layer 20 provided at an inner surface of the pot body. The non-adhesive coating layer is a nano metal ceramic layer that is formed with super-high speed laser welding hardening. Or the non-adhesive coating layer is obtained by stacking the nano metal ceramic layer that is formed with super-high speed laser welding hardening and a nano-ceramic new material formed by hardening. Or the non-adhesive coating layer is configured by stacking the nano metal ceramic layer that is formed with super-high speed laser welding hardening and a nano-ceramic new material formed by hardening alternately a plurality of times. A laser titanium cooker includes a non-adhesive coating layer that is endurant non-adhesive, has high hardness, and is wear resistant.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of ultra-hard and ultra-wear-resistant cookware, and in particular to laser titanium cookware and its manufacturing method. [Background technology]

[0002] The surface of the coated non-stick pan is usually coated with a paint having non-stick properties to achieve the non-stick function. The materials used for the non-stick coating layer of conventional pan utensils mainly include fluorine-containing paint and ceramic paint. Fluorine-containing paints mainly include PTFE (polytetrafluoroethylene), PFOA (ammonium perfluorooctanoate), PFAS (copolymer of perfluoropropyl perfluorovinyl ether and polytetrafluoroethylene), FEP (polyperfluoroethylene propylene copolymer), ETFE (ethylene tetrafluoroethylene copolymer), etc., and their non-stick principle utilizes the extremely low surface free energy and low friction coefficient of fluorine-containing polymers. However, the non-stick coating layer of fluorine-containing paint is weak against wear and easily falls off. In addition, because the surface roughness of the pan body is low, the non-stick coating layer attached to the surface of the pan body is easily scratched or scraped by spatulas or hard foods. This shortens the life of the non-stick coating layer, gradually worsening the non-stickiness of the pan utensils, and eventually losing the non-stickiness. Ceramic paint is a paint mainly composed of silicon-oxygen bond and inorganic silicon, which achieves the non-stick effect by forming a pore-free nano-structure on the surface of the pot body. However, the non-stick pot body of ceramic paint is usually made of aluminum material, and the expansion coefficient of the ceramic coating layer is much lower than that of aluminum, so when it expands or contracts due to heat, the ceramic coating layer is easily cracked. Generally, after 3 to 6 months of use, fine cracks appear on the surface of the coating layer, and the non-stickiness begins to deteriorate.

[0003] In view of the above, current non-stick pans generally have problems such as poor non-stickiness, short life span, and poor high temperature resistance due to the materials themselves. Summary of the Invention [Problem to be solved by the invention]

[0004] The technical problem that the present invention aims to solve is that conventional non-stick pans have poor high temperature resistance, low hardness, poor wear resistance, and short service life. [Means for solving the problem]

[0005] In order to solve the above problems, the present invention proposes the following technical solutions.

[0006] The present invention provides a laser titanium cookware comprising a pot body and a non-stick coating layer provided on the inner surface of the pot body. The non-stick coating layer is a nano metal ceramic layer formed by ultra-high speed laser welding hardening. Alternatively, the non-stick coating layer is obtained by stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a nano ceramic new material formed by hardening. Alternatively, the non-stick coating layer is composed of a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a nano ceramic new material formed by hardening, which are alternately stacked multiple times. The nano metal ceramic layer contains, by mass%, 15-45% titanium metal coated particles and 55-85% nano composite ceramic powder new material. The new nano ceramic material contains, by mass%, 20-30% polymethylsiloxane, 0.5-20% hydroxysilicone oil, 1-5% low melting point glass powder, 6-10% silica sol, 5-10% silicon nitride, 5-10% nano titania, 8-12% nano alumina, 6-8% nano titanium, 3-6% wetting and dispersing agent, 2-4% thickener, and 10-15% water. The new nano composite ceramic powder material contains titanium nitride (TiN), titanium carbide (TiC), silicon carbide (SiC), titanium carbonitride (TiCN), titanium boride (TiB), aluminum oxide (Al2O3), lanthanum oxide (La2O3), yttrium oxide (Y2O3), zirconium oxide (ZrO), magnesium oxide (MgO), calcium hydroxyphosphate (Ca 10The titanium metal-coated particles are at least one of titanium metal (PO4)6(OH)2) and iron powder (Fe). The titanium metal-coated particles have a core-shell structure having three layers. The shell layer is titanium metal, the core layer is silicone oil, and a resin layer is provided between the shell layer and the core layer. The resin layer is a mixture of polymethylsiloxane and iron powder. In terms of mass%, the titanium metal accounts for 10 to 40%, the polymethylsiloxane accounts for 55 to 70%, the iron powder accounts for 0.5 to 2%, and the remainder is silicone oil.

[0007] The SiO2 mass fraction in the silica sol is 1 to 50%, and the average particle size of SiO2 is in the range of 1 nm to 500 nm.

[0008] Furthermore, the titanium metal-coated particles are titanium powder having a nanoscale titanium metal and iron powder having a nanoscale iron powder, and specifically, can be produced by the following procedure. 1. Nanoscale iron powder is added to polymethylsiloxane and dispersed uniformly to obtain a resin solution. 2. The resin solution and silicone oil are mixed by fine emulsion polymerization to produce resin particles of resin-coated silicone oil with a smooth surface and uniform particle size distribution. 3. The resin particles are atomized into nano-scale titanium metal, and the nano-titanium metal is uniformly attached to the surface of the resin particles, so that the titanium metal completely coats the resin particles, and the titanium metal-coated particles are obtained.

[0009] Silicone oil has non-stickiness but poor heat resistance. Silicone oil is coated with a resin containing iron powder, and then coated with titanium metal to obtain titanium metal-coated particles. The titanium metal melts by endothermic heat under high temperature curing by ultra-high speed laser welding, protecting the resin and silicone oil, and the resin and silicone oil can be stored in the coating layer. In the nano-metal ceramic layer containing the titanium metal-coated particles, the resin expands thermally during the heating process when the cookware is used, and the silicone oil seeps out through the pores of the resin, enhancing the non-stickiness effect of the nano-metal ceramic layer. The addition of iron powder helps to increase the heat resistance of the resin layer.

[0010] It is worth noting that the addition of titanium metal-coated particles in the nano-metal ceramic layer helps to improve the non-stickiness of the coating layer, and the ratio is preferably 15-45%, more preferably 20-35%. If the amount is too low, the non-stick effect of the nano-metal ceramic layer will be poor, and if the amount is too high, it will affect the bonding effect of the nano-metal ceramic layer and the nano-ceramic new material.

[0011] Furthermore, the surface of the non-stick coating layer away from the pan body is a nano ceramic new material, and the surface of the non-stick coating layer attached to the pan body is a nano metal ceramic layer.

[0012] In addition, in the nanoceramic new material, the wetting and dispersing agent can be selected from sodium tego tripolyphosphate, and the thickener can be selected from HASE thickeners. Those skilled in the art can select them based on their technical common sense, and the present invention is not limited thereto.

[0013] Furthermore, in order to obtain a high hardness nano-metal ceramic layer, the nano-composite ceramic powder new material is titanium nitride (TiN), titanium carbide (TiC), silicon carbide (SiC), titanium carbonitride (TiCN), titanium boride (TiB), aluminum oxide (Al2O3), lanthanum oxide (La2O3), yttrium oxide (Y2O3), zirconium oxide (ZrO), magnesium oxide (MgO), calcium hydroxyphosphate (Ca 10 (PO4)6(OH)2), and iron powder (Fe).

[0014] Furthermore, the particle size of the new nano-composite ceramic powder material is 0.01-6 μm, and the particle size of the titanium metal-coated particles is 2-6 μm.

[0015] Furthermore, the thickness of the non-adhesive coating layer is 30 to 1000 μm. For example, the thickness of the non-adhesive coating layer is 30 μm, 80 μm, 100 μm, 200 μm, 500 μm, 800 μm, or 1000 μm.

[0016] Furthermore, the thickness of the nano metal ceramic layer is 5 to 20 μm. For example, the thickness of the nano metal ceramic layer is 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, or 20 μm.

[0017] The nano metal ceramic layer is characterized by high hardness and low toughness. The bottom of the pot needs to be shaped during the process of forming the cookware, and if the single-layer nano metal ceramic layer is too thick, its toughness is poor, so cracks may occur in the nano metal ceramic layer, resulting in quality problems. Therefore, the thickness of the single-layer nano metal ceramic layer should not be too thick, and is preferably 5 to 20 μm. This thickness range can prevent the coating layer from cracking when the bottom of the pot is shaped.

[0018] Furthermore, the thickness of the nano ceramic new material is 1 to 8 μm. For example, the thickness of the nano ceramic new material is 1 μm, 2 μm, 5 μm, or 8 μm.

[0019] Furthermore, a superconducting magnetic layer having a thickness of 300 to 600 μm is provided on the outer surface of the pot. For example, the thickness of the superconducting magnetic layer is 300 μm, 400 μm, 500 μm, or 600 μm. Specifically, the superconducting magnetic layer is located at the bottom of the outer surface of the pot.

[0020] Furthermore, in mass %, the superconducting magnetic layer contains 80 to 92% nickel-iron alloy, 0.03 to 2.5% toner, 2 to 6% graphene, 1 to 3.5% chromium powder, 4 to 6% molybdenum powder, and 0.5 to 3% copper powder, and the mass content of nickel in the nickel-iron alloy is 65 to 79%.

[0021] Furthermore, the material of the pot body is any one of aluminum, iron, stainless steel, copper, titanium, and ceramic.

[0022] The present invention also provides a method for manufacturing the laser titanium cookware according to the first aspect, comprising the steps of sandblasting a clean pan body and producing a non-stick coating layer on the inner surface of the pan body. The manufacturing method of the non-adhesive coating layer includes heating the pot body to 120 to 180°C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer of a predetermined thickness, and then performing high temperature welding hardening at 293 to 1693°C to obtain a non-adhesive coating layer. Alternatively, the manufacturing method of the non-adhesive coating layer includes heating the pot body to 120 to 180°C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer, hardening the paint of the nano ceramic new material on the nano metal ceramic layer to obtain a nano ceramic new material, and then performing high temperature welding hardening at 293 to 1693°C to obtain a non-adhesive coating layer having a predetermined thickness. Alternatively, the manufacturing method of the non-adhesive coating layer includes heating the pot body to 120 to 180°C and performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer (S2), hardening a paint of a nano ceramic new material on the nano metal ceramic layer to obtain a nano ceramic new material (S3), and repeating steps S2 to S3 until a predetermined thickness is reached, and performing high temperature welding hardening at 293 to 1693°C to produce a non-adhesive coating layer.

[0023] Specifically, the ultrafast laser welding hardening of the nano metal ceramic layer includes the following: After heating the pan body to 120-180°C, the powder material of the nano metal ceramic layer is laser-hardened on the inner surface of the dry and clean pan body. The hardening process parameters are: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon gas flow rate 20-30L / min, powder feed rate 8g / min. After natural cooling for 15-20 seconds, a laser-hardened coating layer is formed on the inner surface of the pan body, and the surface of the laser-hardened coating layer is cleaned with argon gas at a pressure of 1-2MPa, and then ultrafast laser rewelding is performed to obtain the nano metal ceramic layer. The process parameters of the ultrafast laser rewelding are: power 100-250W, scanning speed 10-12mm / s, spot diameter 4-6mm, argon gas flow rate 20-30L / min.

[0024] Specifically, the process of curing the paint of the nano ceramic new material on the nano metal ceramic layer to obtain the nano ceramic new material includes the following: After obtaining the nano metal ceramic layer by the ultrafast laser re-welding process, purify with argon gas at a pressure of 1.0-2.0Mpa within 20-30 seconds to cure the paint of the nano ceramic new material; Set the distance between the spray gun and the surface of the pot body to 15-30cm to ensure that the paint of the nano ceramic new material covers all the nano metal ceramic layer; Use the residual heat of the ultrafast laser re-welding technology to cure the paint of the nano ceramic new material to obtain the nano ceramic new material.

[0025] Specifically, the non-adhesive coating layer is formed by alternating multiple layers of nano metal ceramic layers formed by ultrafast laser welding and hardening and nano ceramic new materials formed by hardening. During manufacturing, the nano metal ceramic layers and nano ceramic new materials are alternately processed on the inside of the pot through 2 to 50 cycles, with steps S2 to S3 being one cycle, to reach a preset thickness. The non-adhesive coating layer is obtained. In actual implementation, the time interval between the laser thermal hardening in step S2 and ultrafast laser re-welding in each cycle is 10 to 20 seconds, the time interval between the ultrafast laser re-welding and hardening in step S3 is 20 to 30 seconds, and the time interval between each cycle is 30 to 50 seconds. This can greatly improve the processing efficiency under the premise of ensuring the process quality.

[0026] In the manufacturing method, the high temperature welding hardening is performed to further harden and bond the non-adhesive coating layer to the pot body, thereby increasing the bonding strength between them, and the temperature depends on the material of the pot body. For example, if the material of the pot body is stainless steel, the high temperature welding hardening temperature is between 1100 and 1300°C. If the material of the pot body is aluminum, the high temperature welding hardening temperature is 293 to 500°C.

[0027] As can be understood, in the manufacturing method of the present invention, the thermal energy used to manufacture the non-adhesive coating layer is an ultrafast laser, but the scope of protection of the present invention is not limited to manufacturing techniques using laser energy, but also includes manufacturing techniques using heat sources such as laser plasma, plasma, and electron beam.

[0028] The method further includes ultra-high speed laser deposition hardening of the superconducting magnetic layer on the outer surface of the pot body.

[0029] Specifically, the powder material of the superconducting magnetic layer is laser-thermally cured on the outer surface of the pot. The process parameters of the curing are: power 1.5-2kW, scanning speed 8-12mm / s, spot diameter 3mm, argon gas flow rate 20-30L / min, and powder feed rate 8g / min. After natural cooling for 15-20 seconds, a laser-thermally cured coating layer is formed on the outer surface of the pot, and the surface of the laser-thermally cured coating layer is cleaned with argon gas at a pressure of 1-2MPa, and then ultra-high speed laser rewelding is performed to obtain a superconducting magnetic layer. The process parameters of the ultra-high speed laser rewelding are: power 100-250W, scanning speed 10-12mm / s, spot diameter 4-6mm, and argon gas flow rate 20-30L / min.

[0030] In another implementation, the overall manufacturing method for producing the laser titanium cookware includes: 1) stretch forming the wafer; 2) edge processing; 3) cleaning; 4) sandblasting; 5) fabricating a non-stick coating layer; 6) inner polishing; 7) outer sanding; 8) ultra-fast laser welding curing of the superconducting magnetic layer fabricated according to the implementation method and parameters of step S5; 9) sanding; 10) curing; 11) assembly; and 12) packaging.

[0031] The laser titanium cookware provided by the present invention includes all tableware and cookware.

[0032] Preferably, the non-adhesive coating layer of the present invention is composed of multiple alternating nano metal ceramic layers formed by ultra-high speed laser welding and curing and nano ceramic new materials formed by curing. Effect of the Invention

[0033] Compared with the prior art, the technical advantages that the present invention can achieve include: The laser titanium cookware provided by the present invention includes a pot body and a non-sticky coating layer on the inner surface of the pot body. The non-sticky coating layer is a nano metal ceramic layer formed by ultra-high speed laser welding hardening. Or, the non-sticky coating layer is obtained by stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a nano ceramic new material formed by hardening. Or, the non-sticky coating layer is composed of a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a nano ceramic new material formed by hardening, which are alternately stacked multiple times. The nano metal ceramic layer includes titanium metal-coated particles coated with resin and silicone oil, and when combined with a nano composite ceramic powder new material and subjected to ultra-high speed laser welding hardening, the resin and silicone oil in the titanium metal-coated particles can be effectively stored in the coating layer, so that the nano metal ceramic layer has both high hardness and non-stickiness. The new nano ceramic material is formed on the surface of the nano ceramic layer through a curing process by combining components such as polymethylsiloxane, hydroxysilicone oil, low melting point glass powder, silica sol, silicon nitride, nano titania, nano alumina, nano titanium, etc., and also has the effects of high hardness and non-stickiness. In a preferred embodiment, the nano metal ceramic layer and the new nano ceramic material are alternately layered to achieve the effects of high hardness, wear resistance, and long-lasting non-stickiness of the non-stick coating layer.

[0034] In addition, the laser titanium cookware of the present invention is manufactured by first carrying out ultra-high speed laser welding and hardening to form a nano metal ceramic layer, and then using the residual heat effect of laser welding to harden the surface of the nano metal ceramic layer to form a nano ceramic new material, which improves the adhesion effect of the nano ceramic new material and enhances the bonding strength of the two coating layers. At the same time, the components of the nano metal ceramic layer and the nano ceramic new material have a certain similarity, which is favorable for the bonding between the two coating layers. In a preferred embodiment, the non-stick coating layer is obtained by alternately stacking the above two coating layers multiple times, and the two coating layers have both high hardness and non-stickiness. In addition, the bonding strength between the two is strong, and the non-stick coating layer achieves the effects of high hardness, wear resistance, and long-lasting non-stickiness. [Brief description of the drawings]

[0035] In order to more clearly describe the technical aspects of the embodiments of the present invention, the following briefly describes the drawings that need to be used in the description of the embodiments. Obviously, the drawings in the following description are some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without paying creative labor.

[0036] [Figure 1] FIG. 1 is a structural schematic diagram of a laser titanium cookware according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a partially enlarged schematic diagram of A in FIG. [Diagram 3] FIG. 2 is a structural schematic diagram of a non-stick coating layer of a laser titanium cookware according to an embodiment of the present invention. [Figure 4] 1 is a schematic diagram of the structure of a titanium metal coated particle according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] The technical aspects of the embodiments will be described below clearly and completely in conjunction with the drawings in the embodiments of the present invention. Similar component numbers in the drawings represent similar components. It is clear that the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments that can be obtained by those skilled in the art without creative labor belong to the scope of protection of the present invention.

[0038] As used in this specification and the appended claims, the terms "comprises" and "comprising" are to be understood as indicating the presence of stated features, wholes, steps, operations, elements and / or components, but not excluding the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or sets thereof.

[0039] It should also be understood that the terminology used in the description of the embodiments of the present invention is for the purpose of describing particular embodiments only, and is not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise.

[0040] Example 1 With reference to Figures 1-3, an embodiment of the present invention provides a laser titanium cookware. As is clear from the figures, the laser titanium cookware includes a pot body 10, a non-adhesive coating layer 20 provided on the inner surface of the pot body, and a superconducting magnetic layer 30 provided on the outer surface of the pot body. The non-adhesive coating layer 20 is composed of a nano-metal ceramic layer 21 formed by ultra-high speed laser welding hardening and a nano-ceramic new material 22 formed by hardening, which are alternately layered multiple times. Here, the surface of the non-adhesive coating layer 20 away from the pot body 10 is the nano-ceramic new material 22, and the surface of the non-adhesive coating layer 20 attached to the pot body 10 is the nano-metal ceramic layer 21.

[0041] The nano-metal ceramic layer contains, by mass%, 30% titanium metal-coated particles and 70% nano-composite ceramic powder new material. The nano-composite ceramic powder new material is TiN, TiC, SiC, TiCN, TiB, Al2O3, La2O3, Y2O3, ZrO, MgO, Ca 10 (PO4)6(OH)2, Fe.

[0042] The new nanoceramic material consists, by mass, of 25% polymethylsiloxane, 10% hydroxysilicone oil, 3% low-melting point glass powder, 10% silica sol, 7% silicon nitride, 10% nano titania, 10% nano alumina, 7% nano titanium, 3% wetting and dispersing agent, 3% thickener, and 12% water.

[0043] 4, the titanium metal-coated particle has a core-shell structure having three layers, where shell layer 41 is titanium metal, core layer 43 is silicone oil, and between shell layer 41 and core layer 43 is resin layer 42, which is a mixture of polymethylsiloxane and iron powder. In terms of mass%, titanium metal accounts for 30%, polymethylsiloxane accounts for 58%, iron powder accounts for 2%, and the remainder is silicone oil.

[0044] In this embodiment, the titanium metal coated particles are nanoscale titanium powder and nanoscale iron powder, and specifically, can be produced by the following procedure. 1. Nanoscale iron powder is added to polymethylsiloxane and dispersed uniformly to obtain a resin solution. 2. The resin solution and silicone oil are mixed by fine emulsion polymerization to produce resin particles of resin-coated silicone oil with a smooth surface and uniform particle size distribution. 3. The resin particles are atomized into nano-scale titanium metal, and the nano-titanium metal is uniformly attached to the surface of the resin particles, so that the titanium metal completely coats the resin particles, and the titanium metal-coated particles are obtained.

[0045] In this embodiment, the thickness of the superconducting magnetic layer is 500 μm, the components of the superconducting magnetic layer are 85% nickel-iron alloy, 1.8% toner, 4% graphene, 2.2% chromium powder, 5% molybdenum powder, and 2% copper powder, the mass content of nickel in the nickel-iron alloy is 70%, and the particle size of the above powder is 0.01 to 6 microns.

[0046] In this embodiment, the particle size of the nano-composite ceramic powder new material is 0.01-6 microns, and the particle size of the titanium metal-coated particles is 2-6 microns.

[0047] In this embodiment, the thickness of the non-stick coating layer is 300 μm, where the thickness of the nano metal ceramic layer is 10 μm and the thickness of the nano ceramic new material is 5 μm, which are alternately stacked 20 times.

[0048] In this embodiment, the pot body is made of stainless steel.

[0049] An embodiment of the present invention also provides a method for manufacturing the above laser titanium cookware, comprising the following steps. S1, the clean pot body is sandblasted. S2. Heat the pot body to 120~180℃ and perform ultra-high speed laser welding hardening of the nano metal ceramic layer. S3, coating a nano-ceramic new material on the nano-metal-ceramic layer. S4: Steps S2 to S3 are repeated until a preset thickness is reached, and high-temperature welding and hardening is performed at 1200° C. to produce a non-adhesive coating layer. S5. Ultra-high speed laser welding hardening of a superconducting magnetic layer is performed on the outer surface of the pot body.

[0050] Specifically, in this embodiment, in step S2, the pot body is heated to 180°C, and then the powder material of the nano metal ceramic layer is laser-cured on the inner surface of the dry and clean pot body. The process parameters of the curing are power 1.8kW, scanning speed 10mm / s, spot diameter 3mm, argon gas flow rate 25L / min, and powder feed rate 8g / min. After natural cooling for 15 seconds, a laser-cured coating layer is formed on the inner surface of the pot body, and the surface of the laser-cured coating layer is cleaned with argon gas at a pressure of 1.3MPa, and then ultra-high speed laser re-welding is performed to obtain the nano metal ceramic layer. The process parameters of the ultra-high speed laser re-welding are power 250W, scanning speed 12mm / s, spot diameter 5mm, and argon gas flow rate 28L / min.

[0051] Specifically, in this embodiment, in step S3, after the nano metal ceramic layer is obtained by the ultrafast laser re-welding process, it is cleaned with argon gas at a pressure of 1.0 MPa within 20 seconds, and the paint of the nano ceramic new material is cured. The distance between the spray gun and the surface of the pot is set to 15 cm to ensure that the paint of the nano ceramic new material covers all the nano metal ceramic layer. The residual heat of the ultrafast laser re-welding technology is used to harden the paint of the nano ceramic new material, and the nano ceramic new material is obtained.

[0052] Specifically, in this embodiment, in step S5, the powder material of the superconducting magnetic layer is laser-thermally cured on the outer surface of the pot body. The process parameters of the curing are: power 1.5 kW, scanning speed 8 mm / s, spot diameter 3 mm, argon gas flow rate 25 L / min, and powder feed rate 8 g / min. After natural cooling for 15 seconds, a laser-thermally cured coating layer is formed on the outer surface of the pot body, and the surface of the laser-thermally cured coating layer is cleaned with argon gas at a pressure of 1 to 2 MPa, and then ultra-high speed laser re-welding is performed to obtain a superconducting magnetic layer. The process parameters of the ultra-high speed laser re-welding are: power 250 W, scanning speed 12 mm / s, spot diameter 4 mm, and argon gas flow rate 20 L / min.

[0053] In another embodiment, the overall manufacturing method for manufacturing the laser titanium cookware includes: 1) stretch forming the wafer; 2) edge processing; 3) cleaning; 4) sandblasting; 5) implementation methods and parameters of steps S2 to S4; 6) inner polishing; 7) outer sanding; 8) ultra-fast laser welding hardening of the superconducting magnetic layer manufactured according to the implementation methods and parameters of step S5; 9) sanding; 10) hardening; 11) assembly; and 12) packaging.

[0054] Example 2 A laser titanium cookware according to an embodiment of the present invention includes a pot body, a non-stick coating layer provided on the inner surface of the pot body, and a superconducting magnetic layer provided on the outer surface of the pot body. The non-stick coating layer is composed of nano metal ceramic layers formed by ultra-high speed laser welding and hardening and nano ceramic new material formed by hardening, which are alternately layered multiple times. Here, the surface of the non-stick coating layer away from the pot body is the nano ceramic new material, and the surface of the non-stick coating layer attached to the pot body is the nano metal ceramic layer.

[0055] The nano-metal ceramic layer contains, by mass%, 25% titanium metal-coated particles and 75% nano-composite ceramic powder new material. The nano-composite ceramic powder new material is TiN, TiC, SiC, TiCN, TiB, Al2O3, La2O3, Y2O3, ZrO, MgO, Ca 10 (PO4)6(OH)2, Fe.

[0056] The new nanoceramic material contains, by mass, 25% polymethylsiloxane, 10% hydroxysilicone oil, 3% low-melting point glass powder, 10% silica sol, 7% silicon nitride, 10% nano titania, 10% nano alumina, 7% nano titanium, 3% wetting and dispersing agent, 3% thickener, and 12% water.

[0057] The titanium metal-coated particles have a core-shell structure having three layers, the shell layer is titanium metal, the core layer is silicone oil, and between the shell layer and the core layer is a resin layer, the resin layer is a mixture of polymethylsiloxane and iron powder. In terms of mass%, the titanium metal accounts for 30%, the polymethylsiloxane accounts for 58%, the iron powder accounts for 2%, and the remainder is silicone oil.

[0058] In this embodiment, the titanium metal coated particles are made of nanoscale titanium powder and nanoscale iron powder, and can be specifically produced by the following procedure. 1. Nanoscale iron powder is added to polymethylsiloxane and dispersed uniformly to obtain a resin solution. 2. Using the fine emulsion polymerization method, particles with a smooth surface and uniform particle size distribution are prepared to obtain resin particles of resin-coated silicone oil. 3. The resin particles are atomized into nano-scale titanium metal, and the nano-titanium metal is uniformly attached to the surface of the resin particles, so that the titanium metal completely coats the resin particles, and the titanium metal-coated particles are obtained.

[0059] In this embodiment, the thickness of the superconducting magnetic layer is 450 μm, and the components of the superconducting magnetic layer are 85% nickel-iron alloy, 1.8% toner, 4% graphene, 2.2% chromium powder, 5% molybdenum powder, and 2% copper powder, and the mass content of nickel in the nickel-iron alloy is 70%.

[0060] In this embodiment, the particle size of the nano-composite ceramic powder new material is 0.01-6 microns, and the particle size of the titanium metal-coated particles is 2-6 microns.

[0061] In this embodiment, the thickness of the non-stick coating layer is 300 μm, where the thickness of the nano metal ceramic layer is 8 μm and the thickness of the nano ceramic new material is 7 μm, which are alternately stacked 20 times.

[0062] In this embodiment, the pot body is made of stainless steel.

[0063] An embodiment of the present invention also provides a method for manufacturing the above laser titanium cookware, comprising the following steps. S1, the clean pot body is sandblasted. S2. Heat the pot body to 120~180℃ and perform ultra-high speed laser welding hardening of the nano metal ceramic layer. S3, coating a nano-ceramic new material on the nano-metal-ceramic layer. S4: Steps S2 to S3 are repeated until a preset thickness is reached, and high-temperature welding and hardening is performed at 1200° C. to produce a non-adhesive coating layer. S5. Ultra-high speed laser welding hardening of a superconducting magnetic layer is performed on the outer surface of the pot body.

[0064] Specifically, in this embodiment, in step S2, the pot body is heated to 150°C, and then the powder material of the nano metal ceramic layer is laser-cured on the dry and clean inner surface of the pot body. The process parameters of the curing are: power 2.0kW, scanning speed 11mm / s, spot diameter 3mm, argon gas flow rate 25L / min, and powder feed rate 8g / min. After natural cooling for 15 seconds, a laser-cured coating layer is formed on the inner surface of the pot body, and the surface of the laser-cured coating layer is cleaned with argon gas at a pressure of 1.3MPa, and then ultra-high speed laser re-welding is performed to obtain a nano metal ceramic layer. The process parameters of the ultra-high speed laser re-welding are: power 250W, scanning speed 12mm / s, spot diameter 5mm, and argon gas flow rate 28L / min.

[0065] Specifically, in step S3, after the nano metal ceramic layer is obtained by the ultrafast laser re-welding process, it is cleaned with argon gas at a pressure of 1.0 MPa within 20 seconds, and the paint of the nano ceramic new material is cured. The distance between the spray gun and the surface of the pot is set to 15 cm to ensure that the paint of the nano ceramic new material covers all the nano metal ceramic layer. The residual heat of the ultrafast laser re-welding technology is used to harden the paint of the nano ceramic new material, and the nano ceramic new material is obtained.

[0066] Specifically, in step S5, the powder material of the superconducting magnetic layer is laser-cured on the outer surface of the pot body. The process parameters of the curing are: power 1.8 kW, scanning speed 8 mm / s, spot diameter 3 mm, argon gas flow rate 25 L / min, and powder feed rate 8 g / min. After natural cooling for 15 seconds, a laser-cured coating layer is formed on the outer surface of the pot body, and the surface of the laser-cured coating layer is cleaned with argon gas at a pressure of 1 to 2 MPa, and then ultra-high speed laser rewelding is performed to obtain a superconducting magnetic layer. The process parameters of the ultra-high speed laser rewelding are: power 250 W, scanning speed 11 mm / s, spot diameter 4 mm, and argon gas flow rate 20 L / min.

[0067] In another embodiment, the overall manufacturing method for manufacturing the laser titanium cookware includes: 1) stretch forming the wafer; 2) edge processing; 3) cleaning; 4) sandblasting; 5) implementation methods and parameters of steps S2 to S4; 6) inner polishing; 7) outer sanding; 8) ultra-fast laser welding hardening of the superconducting magnetic layer manufactured according to the implementation methods and parameters of step S5; 9) sanding; 10) hardening; 11) assembly; and 12) packaging.

[0068] Example 3 The embodiment of the present invention provides a laser titanium cookware and its manufacturing method, which includes a pan body, a non-stick coating layer on the inner surface of the pan body, and a superconducting magnetic layer on the outer surface of the pan body. The non-stick coating layer is composed of nano metal ceramic layers formed by ultra-high speed laser welding and hardening and nano ceramic new material formed by hardening, which are alternately layered multiple times. Here, the surface of the non-stick coating layer away from the pan body is the nano ceramic new material, and the surface of the non-stick coating layer attached to the pan body is the nano metal ceramic layer.

[0069] The nano metal ceramic layer contains, by mass%, 20% titanium metal coated particles and 80% nano composite ceramic powder new material. The nano composite ceramic powder new material is TiN, TiC, SiC, TiCN, TiB, Al2O3, La2O3, Y2O3, ZrO, MgO, Ca 10 (PO4)6(OH)2, Fe.

[0070] The new nanoceramic material contains, by mass, 25% polymethylsiloxane, 10% hydroxysilicone oil, 3% low-melting point glass powder, 10% silica sol, 7% silicon nitride, 10% nano titania, 10% nano alumina, 7% nano titanium, 3% wetting and dispersing agent, 3% thickener, and 12% water.

[0071] The titanium metal-coated particles have a core-shell structure having three layers, the shell layer is titanium metal, the core layer is silicone oil, and between the shell layer and the core layer is a resin layer, the resin layer is a mixture of polymethylsiloxane and iron powder. In terms of mass%, the titanium metal accounts for 30%, the polymethylsiloxane accounts for 58%, the iron powder accounts for 2%, and the remainder is silicone oil.

[0072] In this embodiment, the titanium metal coated particles are made of nanoscale titanium powder and nanoscale iron powder, and can be specifically produced by the following procedure. 1. Nanoscale iron powder is added to polymethylsiloxane and dispersed uniformly to obtain a resin solution. 2. Using the fine emulsion polymerization method, particles with a smooth surface and uniform particle size distribution are prepared to obtain resin particles of resin-coated silicone oil. 3. The resin particles are atomized into nano-scale titanium metal, and the nano-titanium metal is uniformly attached to the surface of the resin particles, so that the titanium metal completely coats the resin particles, and the titanium metal-coated particles are obtained.

[0073] In this embodiment, the thickness of the superconducting magnetic layer is 400 μm, and the components of the superconducting magnetic layer are 85% nickel-iron alloy, 1.8% toner, 4% graphene, 2.2% chromium powder, 5% molybdenum powder, and 2% copper powder, and the mass content of nickel in the nickel-iron alloy is 70%.

[0074] In this embodiment, the particle size of the new nano-composite ceramic powder material is 0.01-6 microns, and the particle size of the titanium metal-coated particles is 2-6 microns.

[0075] In this embodiment, the thickness of the non-stick coating layer is 150 μm, the thickness of the nano metal ceramic layer is 12 μm, and the thickness of the nano ceramic new material is 3 μm, which are alternately stacked 10 times.

[0076] In this embodiment, the pot body is made of aluminum.

[0077] An embodiment of the present invention also provides a method for manufacturing the above laser titanium cookware, comprising the following steps. S1, the clean pot body is sandblasted. S2. Heat the pot body to 120~180℃ and perform ultra-high speed laser welding hardening of the nano metal ceramic layer. S3, coating a nano-ceramic new material on the nano-metal-ceramic layer. S4: Steps S2 to S3 are repeated until a preset thickness is reached, and high-temperature welding and curing is performed at 450° C. to produce a non-adhesive coating layer. S5. Ultra-high speed laser welding hardening of a superconducting magnetic layer is performed on the outer surface of the pot body.

[0078] Specifically, in this embodiment, in step S2, the pot body is heated to 160°C, and then the powder material of the nano metal ceramic layer is laser-cured on the dry and clean inner surface of the pot body. The process parameters of the curing are: power 2.0kW, scanning speed 10mm / s, spot diameter 3mm, argon gas flow rate 25L / min, and powder feed rate 8g / min. After natural cooling for 15 seconds, a laser-cured coating layer is formed on the inner surface of the pot body, and the surface of the laser-cured coating layer is cleaned with argon gas at a pressure of 1.5MPa, and then ultra-high speed laser re-welding is performed to obtain a nano metal ceramic layer. The process parameters of the ultra-high speed laser re-welding are: power 200W, scanning speed 12mm / s, spot diameter 5mm, and argon gas flow rate 28L / min.

[0079] Specifically, in step S3, after the nano metal ceramic layer is obtained by the ultrafast laser re-welding process, it is cleaned with argon gas at a pressure of 1.0 MPa within 20 seconds, and the paint of the nano ceramic new material is cured. The distance between the spray gun and the surface of the pot is set to 15 cm to ensure that the paint of the nano ceramic new material covers all the nano metal ceramic layer. The residual heat of the ultrafast laser re-welding technology is used to harden the paint of the nano ceramic new material, and the nano ceramic new material is obtained.

[0080] Specifically, in step S5, the powder material of the superconducting magnetic layer is laser-thermally cured on the outer surface of the pot body. The process parameters of the curing are: power 1.5 kW, scanning speed 8 mm / s, spot diameter 3 mm, argon gas flow rate 25 L / min, and powder feed rate 8 g / min. After natural cooling for 15 seconds, a laser-thermally cured coating layer is formed on the outer surface of the pot body, and the surface of the laser-thermally cured coating layer is cleaned with argon gas at a pressure of 1 to 2 MPa, and then ultra-high speed laser rewelding is performed to obtain a superconducting magnetic layer. The process parameters of the ultra-high speed laser rewelding are: power 200 W, scanning speed 8 mm / s, spot diameter 4 mm, and argon gas flow rate 20 L / min.

[0081] In another embodiment, the overall manufacturing method for manufacturing the laser titanium cookware includes: 1) stretch forming the wafer; 2) edge processing; 3) cleaning; 4) sandblasting; 5) implementation methods and parameters of steps S2 to S4; 6) inner polishing; 7) outer sanding; 8) ultra-fast laser welding hardening of the superconducting magnetic layer manufactured according to the implementation methods and parameters of step S5; 9) sanding; 10) hardening; 11) assembly; and 12) packaging.

[0082] Comparative Example 1 The difference from Example 1 is that the non-adhesive coating layer is a nano metal ceramic layer formed by ultra-high speed laser welding hardening, and does not contain nano ceramic new materials. During production, the nano metal ceramic layer has high hardness and poor toughness, so the resulting cookware cracks during the process of shaping the pot bottom, which does not meet the quality requirements of the product.

[0083] Comparative Example 2 The difference from Example 1 is that the non-adhesive coating layer is a new nano-ceramic material formed by curing, and does not include a nano-metallic ceramic layer.

[0084] Comparative Example 3 The difference from Example 1 is that the composition of the nano metal ceramic layer is 10% titanium metal coated particles and 90% nano composite ceramic powder new material.

[0085] Comparative Example 4 The difference from Example 1 is that the composition of the nano metal ceramic layer is 60% titanium metal coated particles and 40% nano composite ceramic powder new material.

[0086] Comparative Example 5 The difference from Example 1 is that the composition of the nano metal ceramic layer does not contain titanium metal coated particles, and the same proportions of nano titanium powder, resin, and silicone oil are used instead of the titanium metal coated particles.

[0087] Comparative Example 6 The difference from Example 1 is that the thickness of the non-adhesive coating layer is 300 μm, where the thickness of the nano metal ceramic layer is 25 μm, the thickness of the nano ceramic new material is 5 μm, and they are alternately stacked 20 times.

[0088] Comparative Example 7 The difference from Example 1 is that the pot body does not include a superconducting magnetic layer, and the manufacturing method does not include step S5.

[0089] (Performance test) Performance tests were conducted on the cookware provided in Example 1 and Comparative Examples 1 to 7. The test results are shown in Table 1 below.

[0090] The abrasion resistance test method involves applying a static vertical pressure of 3 kg to the cookware using a 3M-7447 sponge, rubbing it back and forth once each, replacing the sponge every 1,000 times, and recording the number of cycles.

[0091] The high temperature resistance test method is to place the cookware in a 350±5℃ incubator for 0.5 hours, then remove it and allow it to cool naturally to room temperature. If the coating layer of the cookware does not show any abnormalities such as discoloration, foaming, dissolution, falling off, or cracking after the test, it is determined that the cookware can withstand this temperature. The incubator temperature is then gradually increased with a temperature gradient of 50℃ to test the maximum usable temperature of the cookware.

[0092] The test method for durable non-stickiness is to heat the surface of the pan to 140℃~150℃, add broken egg liquid, and continue to heat to 190℃~240℃. After the egg white has basically solidified, the egg is turned over with a plastic scoop and the maximum number of times that the non-stick effect can be achieved is recorded.

[0093] The hardness test method is measured in accordance with the provisions of GB / T 40737-2021, and the laser titanium hardness pass standard is 500HV according to the company standard.

[0094] The thermal efficiency test method is to turn on the intelligent program frequency conversion power supply, set the voltage to 220V, press the start switch, and press the display power switch. Add 500ml of room temperature clean water to the sample. Turn on the electromagnetic furnace, adjust the power to the maximum stage and heat until the water boils, record the power and time during boiling, and calculate the thermal efficiency.

[0095] The test methods and standards for the adhesion fastness, heat and quench stability, alkali resistance, acid resistance, and salt water corrosion resistance of the coating layer are all based on the test items and test methods required by the national standard GB / T 2421-1998.

[0096] [Table 1]

[0097] From the results in Table 1, the laser titanium cookware according to Example 1 of the present invention has good hardness and abrasion resistance, can withstand high temperatures of 550°C, and has long-lasting non-stickiness. This is due to the effect of the high hardness, abrasion resistance, and long-lasting non-stickiness of the non-stick coating layer, which is achieved by alternating nano metal ceramic layers and nano ceramic new materials. The cookware of Comparative Example 2 only uses the nano ceramic new material, and has a certain degree of non-stickiness, but has poor abrasion resistance and poor long-lasting non-stickiness. In the cookware of Comparative Example 3, the content of titanium metal-coated particles in the nano metal ceramic layer is low, which affects the hardness and long-lasting non-stickiness of the coating layer. In the cookware of Comparative Example 4, the content of titanium metal-coated particles in the nano metal ceramic layer is high, and the titanium metal-coated particles contain resin and silicone oil, so the binding force between the nano ceramic new material and the nano metal ceramic layer is weak, which affects the hardness and long-lasting non-stickiness of the non-stick coating layer, and also results in low adhesion between the coating layers and poor abrasion resistance. The titanium metal-coated particles in Comparative Example 5 are replaced with the same proportions of nano-titanium powder, resin, and silicone oil. When ultrafast laser welding and hardening is performed, the resin and silicone oil evaporate at high temperatures, and the resulting nano-metal ceramic layer loses its non-sticky effect. Therefore, after the surface layer of the non-sticky coating layer - the nano-ceramic new material wears off, the cookware loses its non-sticky effect. The thickness of the nano-metal ceramic layer in Comparative Example 6 is 25 μm. When shaping the cookware, microcracks occur in this coating layer, and even if the cracks are covered with the nano-ceramic new material, they may crack significantly at high temperatures. From the data of Comparative Example 7, it can be seen that the magnetic permeability of the superconducting magnetic layer is high, which can significantly increase the thermal efficiency of the cookware when in use.

[0098] In the above embodiments, emphasis is placed on the description of each embodiment, and for parts that are not described in detail in one embodiment, reference may be made to the relevant descriptions of other embodiments.

[0099] The above are specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present invention, and these modifications or replacements should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the claims.

[0100] (Additional Note) (Appendix 1) A laser titanium cookware, The pot body and the non-adhesive coating layer provided on the inner surface of the pot body, the non-adhesive coating layer being a nano metal ceramic layer formed by ultra-high speed laser welding hardening, or the non-adhesive coating layer is obtained by stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a new nano ceramic material formed by hardening, or the non-adhesive coating layer is constructed by alternately stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a new nano ceramic material formed by hardening multiple times, The nano metal ceramic layer contains, by mass%, 15 to 45% titanium metal coated particles and 55 to 85% nano composite ceramic powder new material; The nanoceramic new material contains, by mass%, 20-30% polymethylsiloxane, 0.5-20% hydroxysilicone oil, 1-5% low melting point glass powder, 6-10% silica sol, 5-10% silicon nitride, 5-10% nano titania, 8-12% nano alumina, 6-8% nano titanium, 3-6% wetting and dispersing agent, 2-4% thickener, and 10-15% water. The nanocomposite ceramic powder new material is selected from at least one of titanium nitride, titanium carbide, silicon carbide, titanium carbonitride, titanium boride, aluminum oxide, lanthanum oxide, yttrium oxide, zirconium oxide, magnesium oxide, calcium hydroxyphosphate, and iron powder; The titanium metal-coated particles have a core-shell structure having three layers, the shell layer is titanium metal, the core layer is silicone oil, and a resin layer is between the shell layer and the core layer, the resin layer is a mixture of polymethylsiloxane and iron powder, and, in mass%, the titanium metal accounts for 10 to 40%, the polymethylsiloxane accounts for 55 to 70%, the iron powder accounts for 0.5 to 2%, and the remainder is silicone oil. Laser titanium cookware is characterized by:

[0101] (Appendix 2) The particle size of the nano-composite ceramic powder new material is 0.01-6 μm, and the particle size of the titanium metal-coated particles is 2-6 μm; 2. The laser titanium cookware according to claim 1,

[0102] (Appendix 3) The thickness of the non-adhesive coating layer is 30 to 1000 μm. 2. The laser titanium cookware according to claim 1,

[0103] (Appendix 4) The nano metal ceramic layer has a thickness of 5 to 20 μm; 2. The laser titanium cookware according to claim 1,

[0104] (Appendix 5) The thickness of the nanoceramic new material is 1 to 8 μm; 2. The laser titanium cookware according to claim 1,

[0105] (Appendix 6) A superconducting magnetic layer having a thickness of 300 to 600 μm is provided on the outer surface of the pot body. 2. The laser titanium cookware according to claim 1,

[0106] (Appendix 7) In terms of mass%, the superconducting magnetic layer contains 80-92% nickel-iron alloy, 0.03-2.5% toner, 2-6% graphene, 1-3.5% chromium powder, 4-6% molybdenum powder, and 0.5-3% copper powder, and the mass content of nickel in the nickel-iron alloy is 65-79%; The laser titanium cookware according to claim 5, characterized in that

[0107] (Appendix 8) The material of the pot body is any one of aluminum, iron, stainless steel, copper, titanium, and ceramic. 2. The laser titanium cookware according to claim 1,

[0108] (Appendix 9) A method for producing a laser titanium cookware according to any one of claims 1 to 8, The method includes the steps of sandblasting a clean pan body and producing a non-stick coating layer on the inner surface of the pan body, The method for producing the non-adhesive coating layer includes heating the pot body to 120 to 180 ° C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer of a predetermined thickness, and then performing high temperature welding hardening at 293 to 1693 ° C to obtain a non-adhesive coating layer; Alternatively, the method for producing the non-adhesive coating layer includes heating the pot body to 120 to 180°C, performing ultra-high speed laser welding hardening of the powder material of the nano-metal ceramic layer to obtain a nano-metal ceramic layer, hardening the paint of the nano-ceramic new material on the nano-metal ceramic layer to obtain a nano-ceramic new material, and then performing high-temperature welding hardening at 293 to 1693°C to obtain a non-adhesive coating layer having a predetermined thickness; Alternatively, the method for producing the non-adhesive coating layer includes heating the pot body to 120 to 180°C, performing ultra-high speed laser welding hardening of the powder material of the nano-metal ceramic layer to obtain a nano-metal ceramic layer (S2), hardening the paint of the nano-ceramic new material on the nano-metal ceramic layer to obtain a nano-ceramic new material (S3), and repeating steps S2 to S3 to a preset thickness, performing high-temperature welding hardening at 293 to 1693°C to produce a non-adhesive coating layer. A method for manufacturing a laser titanium cookware.

[0109] (Appendix 10) Further comprising performing ultra-high speed laser welding hardening of the superconducting magnetic layer on the outer surface of the pot body; The manufacturing method according to claim 9, [Explanation of symbols]

[0110] 10: pot body, 20: non-adhesive coating layer, 30: superconducting magnetic layer, 21: nano metal ceramic layer, 22: nano ceramic new material, 41: shell layer, 42: resin layer, 43: core layer.

Claims

1. A laser titanium cookware, The pot body and the non-adhesive coating layer provided on the inner surface of the pot body, the non-adhesive coating layer being a nano metal ceramic layer formed by ultra-high speed laser welding hardening, or the non-adhesive coating layer is obtained by stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a new nano ceramic material formed by hardening, or the non-adhesive coating layer is constructed by alternately stacking a nano metal ceramic layer formed by ultra-high speed laser welding hardening and a new nano ceramic material formed by hardening multiple times, The nano metal ceramic layer comprises, by weight, 15-45% titanium metal coated particles and 55-85% nano composite ceramic powder new material; The nanoceramic new material contains, by mass%, 20-30% polymethylsiloxane, 0.5-20% hydroxysilicone oil, 1-5% low melting point glass powder, 6-10% silica sol, 5-10% silicon nitride, 5-10% nano titania, 8-12% nano alumina, 6-8% nano titanium, 3-6% wetting and dispersing agent, 2-4% thickener, and 10-15% water. The nanocomposite ceramic powder new material is selected from at least one of titanium nitride, titanium carbide, silicon carbide, titanium carbonitride, titanium boride, aluminum oxide, lanthanum oxide, yttrium oxide, zirconium oxide, magnesium oxide, calcium hydroxyphosphate, and iron powder; The titanium metal-coated particles have a core-shell structure having three layers, the shell layer being titanium metal, the core layer being silicone oil, and a resin layer being between the shell layer and the core layer, the resin layer being a mixture of polymethylsiloxane and iron powder, and the titanium metal accounts for 10 to 40% by mass, the polymethylsiloxane accounts for 55 to 70% by mass, the iron powder accounts for 0.5 to 2% by mass, and the remainder is silicone oil. Laser titanium cookware is characterized by:

2. The particle size of the nano-composite ceramic powder new material is 0.01-6 μm, and the particle size of the titanium metal-coated particles is 2-6 μm; 2. The laser titanium cookware of claim 1.

3. The thickness of the non-adhesive coating layer is 30 to 1000 μm.

2. The laser titanium cookware of claim 1.

4. The thickness of the nano metal ceramic layer is 5 to 20 μm; 2. The laser titanium cookware of claim 1.

5. The thickness of the nanoceramic new material is 1 to 8 μm; 2. The laser titanium cookware of claim 1.

6. A superconducting magnetic layer having a thickness of 300 to 600 μm is provided on the outer surface of the pot body.

2. The laser titanium cookware of claim 1.

7. In terms of mass%, the superconducting magnetic layer contains 80-92% nickel-iron alloy, 0.03-2.5% toner, 2-6% graphene, 1-3.5% chromium powder, 4-6% molybdenum powder, and 0.5-3% copper powder, and the mass content of nickel in the nickel-iron alloy is 65-79%; 6. The laser titanium cookware of claim 5.

8. The material of the pot body is any one of aluminum, iron, stainless steel, copper, titanium, and ceramic.

2. The laser titanium cookware of claim 1.

9. A method for manufacturing a laser titanium cookware according to any one of claims 1 to 8, The method includes the steps of sandblasting a clean pan body and producing a non-stick coating layer on the inner surface of the pan body, The method for producing the non-sticky coating layer includes heating the pot body to 120-180°C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer of a predetermined thickness, and then performing high temperature welding hardening at 293-1693°C to obtain a non-sticky coating layer; Alternatively, the method for producing the non-sticky coating layer includes heating the pot body to 120-180°C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer, hardening the paint of the new nano ceramic material on the nano metal ceramic layer to obtain a new nano ceramic material, and then performing high temperature welding hardening at 293-1693°C to obtain a non-sticky coating layer having a predetermined thickness; Alternatively, the method for producing the non-adhesive coating layer includes heating the pot body to 120-180°C, performing ultra-high speed laser welding hardening of the powder material of the nano metal ceramic layer to obtain a nano metal ceramic layer (S2), hardening the paint of the nano ceramic new material on the nano metal ceramic layer to obtain a nano ceramic new material (S3), and repeating steps S2-S3 to a preset thickness, performing high temperature welding hardening at 293-1693°C to prepare a non-adhesive coating layer. A method for manufacturing a laser titanium cookware.

10. Further comprising performing ultra-high speed laser welding hardening of the superconducting magnetic layer on the outer surface of the pot body; The method according to claim 9 .

Citation Information

Patent Citations

  • Laser cladding biological metal ceramic pot and preparation method thereof

    CN112176337A

  • Container and cooking utensil

    CN113679253A

  • Cooker with pure inorganic non-stick coating and manufacturing method thereof

    CN115474829A

  • Composite material for cooker, preparation method of composite material and cooker

    CN116268966A